Kajian Putusan No. 54/Pdt.Sus-PHI.G/2020/PN.JKT.PST Tentang Merger Perusahaan dan Akibat Hukum Bagi Pekerja - Rahmah, Alya Baetu; Suhartini, Endeh; Djuniarsono, R. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Examining judgment No. 54/Pdt.Sus-PHI.G/2020/PN.JKT.PST, which addresses business mergers and their legal ramifications for employees, is the goal of this study. The normative legal research approach, which is employed for this study, is conducted by examining relevant literature, statutory rules, and court decisions. The study's findings demonstrate that the ruling upholds the rights of the affected employees and clarifies the legislation that is applicable in the event of business mergers. This ruling might serve as a guide for businesses and employees to comprehend the legal obligations and safeguards that need to be in place during the merger procedure. In addition, this ruling offers guidelines for workers impacted by corporate mergers in terms of dispute resolution proceduresThis study advances knowledge of the legal ramifications of business mergers and labor laws. The findings of this study can serve as recommendations for businesses, employees, and attorneys. This study may be used to circumstances involving corporate mergers while upholding the rights of employees.